Some fixed point theorems on $α$-$β$-$G$-complete $ G $-metric spaces - V.S. Chary; G.S.M. Reddy; H. Isik; H. Aydi; D.S. Chary (Karpatsʹkì Matematičnì Publìkacìï, 2021)
In this manuscript, we initiate the concept of rectangular $α$-$G$-admissible mappings with respect to $β$ and we consider related type contractions in the setting of $G$-metric spaces. We provide some fixed point results. Also, some examples are given to support the obtained results.